1999
DOI: 10.1124/mol.56.5.973
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Individual Subunits to the Multimeric P2X2 Receptor: Estimates based on Methanethiosulfonate Block at T336C

Abstract: P2X receptors are membrane proteins that incorporate a cation-selective ion channel that can be opened by the binding of extracellular ATP. They associate as hetero- and homo-multimers of currently unknown stoichiometry. In this study, we have used Xenopus laevis oocytes to express rat P2X(2) receptor subunits, which carry a cysteine mutation at position 336. ATP-induced currents at this mutant receptor subunit were blocked by more than 90% when exposed to [2-(trimethylammonium) ethyl] methanethiosulfonate (MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 22 publications
10
102
0
Order By: Relevance
“…Receptors-Tags were introduced by overlapping PCR as described previously (8) in the extracellular loop of P2X subunits, all at similar positions; FLAG tags were inserted in P2X 2 and P2X 6 between Asp 78 -Lys 79 and Glu 83 -Lys 84 , respectively; P2X 3 has a Myc tag inserted between residues Asn 104 and Arg 105 ; P2X 4 has an HA tag between Gln 78 and Leu 79 ; and P2X 5 has either a Myc or an HA tag inserted between Thr 78 and Thr 79 . In all cases tag insertions did not alter the function of the different P2X subunits measured electrophysiologically.…”
Section: Insertions Of Extracellular Tags On P2xmentioning
confidence: 99%
See 1 more Smart Citation
“…Receptors-Tags were introduced by overlapping PCR as described previously (8) in the extracellular loop of P2X subunits, all at similar positions; FLAG tags were inserted in P2X 2 and P2X 6 between Asp 78 -Lys 79 and Glu 83 -Lys 84 , respectively; P2X 3 has a Myc tag inserted between residues Asn 104 and Arg 105 ; P2X 4 has an HA tag between Gln 78 and Leu 79 ; and P2X 5 has either a Myc or an HA tag inserted between Thr 78 and Thr 79 . In all cases tag insertions did not alter the function of the different P2X subunits measured electrophysiologically.…”
Section: Insertions Of Extracellular Tags On P2xmentioning
confidence: 99%
“…P2X subunits have a membrane topology with two transmembrane domains linked by a large extracellular loop; N and C termini are localized intracellularly (5,6). To form a channel, P2X subunits are thought to associate as homo-or heterooligomers, composed of three subunits (7,8) organized in a head-to-tail orientation around a central pore (9). This model is consistent with studies that show that the permeation pathway is associated with transmembrane regions (10 -12), and with the fact that the gating of the channel is in part due to movements of the subunits relative to the each other (12).…”
mentioning
confidence: 99%
“…Often native cell types express multiple P2X subunit mRNA transcripts and multiple P2X subunits. It is not clear how many subunits are required in each heteromer, which ones dominate, or if a greater number of heteromers can be formed [78,121,163]. P2X 6 subunits form only heteromeric channels and P2X 7 subunits only homomeric channels [173].…”
Section: Introductionmentioning
confidence: 99%
“…P2X receptors form as multimeric assemblies of channel subunits. The exact stoichiometry of the receptor remains unclear although studies have suggested that the channel may be comprised of at least three subunits [163].…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence indicated that the functional protein was a trimer: indeed, three ATP-binding sites had been suggested by Bean [14] on the basis of his ATP dose-response curves from bullfrog sensory neurons. This evidence included biochemical approaches using blue native polyacrylamide gel electrophoresis [30] and functional approaches with co-expression and concatenation of subunits carrying reporter mutations [31][32][33][34][35]. The demonstration that P2X receptors were trimers set them in clear distinction from the tetrameric glutamate-gated ion channels and the pentameric nicotinic superfamily (which also includes channels gated by glycine, g-aminobutryic acid and 5-hydroxytryptamine; [22]).…”
Section: Following Cdna Cloningmentioning
confidence: 99%